2006
DOI: 10.1136/adc.2005.092320
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of neuropsychological and behavioural outcomes in early childhood survivors of congenital heart disease

Abstract: Aims: To evaluate the relative effect of cyanosis, surgical interventions and family processes on neuropsychological and behavioural outcomes in 4-year-old survivors of serious congenital heart disease (CHD). Methods: 90 children with a range of cyanotic and acyanotic conditions, who underwent either corrective or palliative surgery, completed a neuropsychological and behavioural evaluation. Families of participants were also profiled by evaluation of maternal mental health, worry, social support, parenting st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 15 publications
4
96
1
1
Order By: Relevance
“…However, given previous research demonstrating an increased risk of neurodevelopmental disorders 3,5,6 and psychological maladjustment, 11,47 as well as the strength of the associations in our study, we do not believe that this potential bias explains our results. Psychiatric hospitalization is a recognized outcome measure in research on psychiatric disorders with high validity.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…However, given previous research demonstrating an increased risk of neurodevelopmental disorders 3,5,6 and psychological maladjustment, 11,47 as well as the strength of the associations in our study, we do not believe that this potential bias explains our results. Psychiatric hospitalization is a recognized outcome measure in research on psychiatric disorders with high validity.…”
Section: Discussioncontrasting
confidence: 48%
“…43 The results from an Irish study of children with a range of cyanotic and acyanotic defects who underwent either corrective or palliative surgery highlight the sometimes greater relevance of family processes (eg, parenting style, maternal mental health, and worry) rather than disease or surgical factors, in predicting behavioral outcomes in this context. 11 Thus, interactions among several biological and psychological risk factors are likely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that this finding was present in both samples, hence not showing any specific mutual influence from mother to child in families with a child with CHD. Negative effects of maternal distress on child behavior have previously been shown in families of a child with CHD (Gupta et al 1998;Visconti et al 2002;McCusker et al 2007;Spijkerboer et al 2010) and also in families with healthy children (Elgar et al 2004). A study among adolescents with depressive symptoms and antisocial behavior reported a corresponding effect of the same size (Pike et al 1996).…”
Section: Contributions Of Individual and Shared Factors And Mutual Inmentioning
confidence: 99%
“…However, their relative importance has not previously been studied in families with a child with CHD or another life-threatening congenital condition. There are studies available on the negative influence of maternal mental health problems on the child with CHD (Gupta et al 1998;Visconti et al 2002;McCusker et al 2007;Spijkerboer et al 2010), but none of these studies examined the relative importance of individual experiences, shared experiences and mutual influences between the parents and the child. Moreover, there are no studies that address whether the covariation of psychological distress in families of children with CHD is specific for families with a sick child or reflects processes that can also be found in families with healthy children.…”
Section: Introductionmentioning
confidence: 99%